Delta-like ligand 4-targeted nanomedicine for antiangiogenic cancer therapy. (February 2015) - Liu, Ya-Rong; Guan, Ying-Yun; Luan, Xin; Lu, Qin; Wang, Chao; Liu, Hai-Jun; Gao, Yun-Ge; Yang, Si-Cong; Dong, Xiao; Chen, Hong-Zhuan; Fang, Chao
Abstract: Tumor angiogenesis is a multistep process involved with multiple molecular events in cancer microenvironment. Several molecular-targeted agents aiming to suppress tumor angiogenesis have been successfully translated into cancer clinic. However, new strategies are still urgently desired to be excavated to overcome the poor response and resistance in some antiangiogenic therapies. Recently, Delta-like ligand 4 (Dll4) is identified to be specifically over-expressed on tumor vascular endothelial cells (EC), and the Dll4-Notch pathway serves as a critical regulator in the development and maintenance of tumor angiogenesis. The intensively up-regulated phenotype of Dll4 on the membrane of tumor vascular EC implies that Dll4 may act as a targetable address for drug delivery system (DDS) to achieve targeted antiangiogenic cancer therapy. Here, a nano-DDS, GD16 peptide (H2 N-GRCTNFHNFIYICFPD-CONH2, containing a disulfide bond between Cys3 and Cys13 ) conjugated nanoparticles loading paclitaxel (GD16-PTX-NP), which can specifically target the angiogenic marker Dll4, was fabricated for the investigation of antiangiogenic therapeutic efficacy in human head and neck cancer FaDu (Dll4-negative) xenograft in nude mice. The results demonstrate that GD16-PTX-NP achieved controlled drug release and exhibited favorable in vivo long-circulating feature. GD16-PTX-NP exerted enhanced antiangiogenic activity in the inhibition of human umbilical vein endothelial cell (HUVEC) viability, motility, migration, and tube formation, and in the Matrigel plug model as well, which can be definitely ascribed to the active internalization mediated by the interaction of GD16 and the over-expressed Dll4 on EC. GD16-PTX-NP showed accurate in vivo tumor neovasculature targeting property in FaDu tumor, where the paclitaxel was specifically delivered into the tumor vascular EC, leading to significant apoptosis of tumor vascular EC and necrosis of tumor tissues. The antiangiogenic activity of GD16-PTX-NP significantly contributed to its in vivo anticancer efficacy in Fadu tumor; moreover, no overt toxicity to the mice was observed. Our research firstly presents the potency and significance of a Dll4-targeted nanomedicine in antiangiogenic cancer therapy.